“Quiero despatriarcalizar mi estantería” o la estética teatral en la dramaturgia de María Velasco - Hernández Pérez, Markel (2024)
In this article, two theatrical works by one of the most recognized contemporary Spanish playwrights, María Velasco, Líbrate de las cosas hermosas que te deseo (2015) and Talaré a los hombres de sobre la faz de la tierra, both premiered and applauded by theater critics, as well as awarded, will be analyzed. The point of convergence of these two works is found in their performative aesthetic and the political and poetic perspective with which they portray the situation of their protagonists. Both dramatic proposals have an innovative and contemporary scenic aesthetic, so we will approach them through the paradigm of performative theater, liminal theater, and perfopoetry, since both are an artistic object that escapes reductionist interpretations due to their multidimensional nature. However, it will be verified that the purpose of the pieces is to portray a political structure, without any of them renouncing the use of a wide range of dramatic possibilities proposed from the text, stage directions, and the corresponding scenic proposal.